2013
DOI: 10.1016/j.foodchem.2012.11.139
|View full text |Cite
|
Sign up to set email alerts
|

A review of the dietary flavonoid, kaempferol on human health and cancer chemoprevention

Abstract: Kaempferol is a polyphenol antioxidant found in fruits and vegetables. Many studies have described the beneficial effects of dietary kaempferol in reducing the risk of chronic diseases, especially cancer. Epidemiological studies have shown an inverse relationship between kaempferol intake and cancer. Kaempferol may help by augmenting the body’s antioxidant defense against free radicals, which promote the development of cancer. At the molecular level, kaempferol has been reported to modulate a number of key ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
514
1
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 839 publications
(536 citation statements)
references
References 79 publications
(95 reference statements)
8
514
1
13
Order By: Relevance
“…Luteolin is known to promote cell death by apoptosis and preservation of normal cells and also possesses significant anticancer properties (Chen & Chen, 2013;Dang et al, 2015;Zheng et al, 2014). Its presence in honey produced by Melipona q. anthidoides and Melipona mandacaia might attribute cell protecting properties.…”
Section: Resultsmentioning
confidence: 99%
“…Luteolin is known to promote cell death by apoptosis and preservation of normal cells and also possesses significant anticancer properties (Chen & Chen, 2013;Dang et al, 2015;Zheng et al, 2014). Its presence in honey produced by Melipona q. anthidoides and Melipona mandacaia might attribute cell protecting properties.…”
Section: Resultsmentioning
confidence: 99%
“…Flavonoids are believed to protect cells from disease by shielding lipids, proteins and DNA from oxidative damage. 52 Previous in vitro bioactivity studies of flavonoids have demonstrated anti-inflammatory, antioxidant, and anticancer activity. 52 The results of this study indicate that the acai, cacao and maca extracts have bacterial growth inhibitory activity and ability to block cancer cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…52 Previous in vitro bioactivity studies of flavonoids have demonstrated anti-inflammatory, antioxidant, and anticancer activity. 52 The results of this study indicate that the acai, cacao and maca extracts have bacterial growth inhibitory activity and ability to block cancer cell proliferation. The good antibacterial activity of acai and maca ethyl acetate extracts and the cancer cell anti-proliferative activity of the aqueous cacao and maca extracts indicates their potential in the treatment of rheumatoid arthritis and some cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenols have become an intense focus of research interest due to their potent antioxidant properties and their perceived health-beneficial effects in the treatment and prevention of cancer, cardiovascular disease, and other pathologies (Chen and Chen 2013;Iriti and Varoni 2013;Martin et al 2013).…”
Section: Introductionmentioning
confidence: 99%